Sexual size dimorphism in golden pompano (Trachinotus blochii): Potential roles of changes in energy allocation and differences in muscle metabolism - Sun, Jun Long; Song, Fei Biao; Wang, Lei; Zhang, Wei Wei; Chen, You Ming; Zhou, Li; Gui, Jian Fang; Luo, Jian (Frontiers in Marine Science, 2022)
Golden pompano (Trachinotus blochii) is becoming increasingly popular and produces high yields, but the growth differences between males and females are a concern. In this study, the differences between the growth of males and females were compared, and the transcriptome analysis of muscle tissues was performed. A significant difference between the growth of males and females was observed; females were found to be 17% larger than males after reaching 7 months of age. Gonadal histological analysis revealed that the ovaries were arrested in 7- to 9-month-old golden pompano, whereas the testes continued to develop. The AMPK and adipocytokine signaling pathways were also found to be involved in the regulation of muscle growth and metabolism. After reaching 7 months of age, the expression levels of glut1, glut4, ldh, gys, acsl and cpt2 in the muscle of females were lower than those in males, but the hk gene, which is involved in glycolysis, was found to remain highly expressed in females. Additionally, in females, the synthesis of arginine and ornithine and the production of carnosine were found to be inhibited, but the breakdown of glutamine was found to be enhanced and OXPHOS ability was found to be stronger in females after reaching 7 months of age. These results support a certain negative correlation between gonadal development and muscle metabolism depending on differences in energy distribution. Clearly, the faster growth in females after reaching 7 months of age was found to be associated with the more active metabolism of glucose, and amino acids, as well as stronger oxidative phosphorylation levels.